2013
DOI: 10.1371/journal.pone.0056509
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Detection from Human Immunodeficiency Virus-Infected Colombian Women's Paired Urine and Cervical Samples

Abstract: Infection, coinfection and type-specific human papillomavirus (HPV) distribution was evaluated in human immunodeficiency virus (HIV)-positive women from paired cervical and urine samples. Paired cervical and urine samples (n = 204) were taken from HIV-positive women for identifying HPV-DNA presence by using polymerase chain reaction (PCR) with three generic primer sets (GP5+/6+, MY09/11 and pU1M/2R). HPV-positive samples were typed for six high-risk HPV (HR-HPV) (HPV-16, -18, -31, -33, -45 and -58) and two low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
1
8
0
2
Order By: Relevance
“…Under these circumstances, testing urine for HPV DNA offers a distinct advantage (Prusty et al, 2005). Previous studies have compared HPV detection rates between cervical and urine samples in order to evaluate the ability of urine-based assays to detect the prevalence of HPV independently of cervical cytology assays (Daponte et al, 2006; Munoz et al, 2013). Evidence suggests that the sensitivity of urine testing for HPV 16 and 18 was higher for participants with cervical cancer (88.8%) than for those with high- and low-grade lesions (Daponte et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, testing urine for HPV DNA offers a distinct advantage (Prusty et al, 2005). Previous studies have compared HPV detection rates between cervical and urine samples in order to evaluate the ability of urine-based assays to detect the prevalence of HPV independently of cervical cytology assays (Daponte et al, 2006; Munoz et al, 2013). Evidence suggests that the sensitivity of urine testing for HPV 16 and 18 was higher for participants with cervical cancer (88.8%) than for those with high- and low-grade lesions (Daponte et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…What is worth noting is that the majority of HPV45 was present in co-infections with HPV16. There are substantial data suggesting that in HIV-positive women there is higher prevalence of HPV and more frequent multiple type co-infections, and one small study in Cameroon comparing HPV infections and HIV status showed HPV45 to be the dominant co-infection type 15 16. More studies are required to address the association between HIV infection and the prevalence of HPV types in women with normal cytology or with ICC.…”
Section: Discussionmentioning
confidence: 99%
“…It was different from a previous survey in Thai women, which reported HPV16 as the most common genotype identified (17.9%) (Chansaenroj et al, 2010). HPV 16 remained the most prevalent HPV genotype in Thailand as well as in many other countries (Onuki et al, 2009;Bissett et al, 2011;Munoz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%